Engineering of Organic Photodetector For Visible Light Detection By Vacuum Thermal Deposition Method - Chairadeya, Chairadeya; Sumanto, Budi; Estrada, Richie; Biring, Sajal; Liu, Shun-Wei (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
This study aimed to determine the correlation between the photoactive layer thickness of an organic photodetector device and its performance. This research engineered organic photodetectors using zinc phthalocyanine (ZnPc) and fullerene (C60) as photoactive layers for detecting visible light using the vacuum thermal deposition method. Fabrication of organic photodetectors is done by varying the thickness of the photoactive layer at the same ratio. Of the four engineered organic photodetector variations, an active layer thickness of 90 nm produced the best organic photodetector performance. This photodetector has a dark current density of 1.43 × 10-6 A cm-2, a photocurrent density of 6.19 × 10-4 A cm-2, an external quantum efficiency (EQE) of 73.48% at a wavelength of 630 nm, with a responsivity of 0.39 A W-1 at a bias voltage of -3 V.